Genome Assembly and Annotation of Soft-Shelled Adlay (Coix lacryma-jobi Variety ma-yuen), a Cereal and Medicinal Crop in the Poaceae Family - Kang, Sang-Ho; Kim, Byeollee; Choi, Beom-Soon; Lee, Hyun Oh; Kim, Nam-Hoon; Lee, Seung Jae; Kim, Hye Sik; Shin, Myung Ju; Kim, Hyo-Won; Nam, Kyunghyun; Kang, Kyoung Dae; Kwon, Soo-Jin; et al. (Frontiers in Plant Science, 2020)
Coix lacryma-jobi, also called adlay or Job’s tears, is an annual herbal plant belonging to the Poaceae family that has been cultivated as a cereal and medicinal crop in Asia. Despite its importance, however, genomic resources for better understanding this plant species at the molecular level and informing improved breeding strategies remain limited. To address this, we generated a draft genome of the C. lacryma-jobi variety ma-yuen (soft-shelled adlay) Korean cultivar, Johyun, by de novo assembly, using PacBio and Illumina sequencing data. A total of 3,362 scaffold sequences, 1.28 Gb in length, were assembled, representing 82.1% of the estimated genome size (1.56 Gb). Genome completeness was confirmed by the presence of 91.4% of the BUSCO angiosperm genes and mapping ratio of 98.3% of Illumina paired-end reads. We found that approximately 77.0% of the genome is occupied by repeat sequences, most of which are Gypsy and Copia-type retrotransposons, and evidence-based genome annotation predicts 39,574 protein-coding genes, 85.5% of which were functionally annotated. We further predict that soft-shelled adlay diverged from a common ancestor with sorghum 9.0-11.2 MYA. Transcriptome profiling revealed 3,988 genes that are differentially expressed in seeds relative to other tissues, of which 1,470 genes were strongly up-regulated in seeds and the most enriched Gene Ontology terms were assigned to carbohydrate and protein metabolism. In addition, we identified 76 storage protein genes including 18 seed-specific coixin genes and 13 candidate genes involved in biosynthesis of benzoxazinoids (BXs) including coixol, a unique BX compound found in C. lacryma-jobi species. The characterization of those genes can further our understanding of unique traits of soft-shelled adlay, such as high seed protein content and medicinal compound biosynthesis. Taken together, our genome sequence data will provide a valuable resource for molecular breeding and pharmacological study of this plant species.